Metode Hamamun Sebagai Salah Satu Bentuk Adaptasi Kurikulum pada Materi Bilangan Bulat: - - Sutarti, S; Andini, Dinar Westri; Irfan, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
In reality, teachers are faced with a diversity of student characteristics, one of which is related to different cognitive abilities. The aim of this research is to determine the successful learning outcomes of all students through the implementation of the Hamamun method